PEMBENTUKAN VARIABEL KUNCI KEBERHASILAN AKADEMIK MAHASISWA JURUSAN TADRIS ILMU PENGETAHUAN SOSIAL - Yeti Nurizzati; Suniti suniti (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2021)
ABSTRACTDepartment of Social Sciences is one of the majors in the Faculty of Tarbiyah and Teacher Training at the Institute of Islamic Studies in the State of Sheikh Nurjati Cirebon. The Department has endeavored to produce graduates on time and a minimum GPA of 3. This can be seen from the almost no drop-out students, at least students who are still active studying in more than semester 8, and the increasing number of students who have graduated in semester 8. Therefore That is the purpose of this research, which is to reveal what variables are key to the academic success of students in the Tadris Department of Social Sciences. Samples were selected from students who succeeded academically in the years 2013 and 2014, totaling 51 people according to the number of responses to the Google form questionnaire answers. This raw data is then processed using descriptive statistics in the form of tables and graphs, percentage analysis, and factor analysis. There are 22 variables out of 35 variables which are the factors of student academic success, with the acquisition of response responses of 75.56%. Through factor analysis, five groups are formed which are the keys to student academic success, namely the ability and habits of students in learning, assessment policies, and the campus environment; the attitude of students and lecturers; family support; student's ability to implement learning outcomes, and curriculum compatibility; and learning motivation.Â Keywords: Key variables, Academic success, Factor analysis